The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/microorganisms11010033
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Shedding of SARS-CoV-2 in Children: No Evidence for Infectious Potential

Abstract: The clinical courses of COVID-19 in children are often mild and may remain undiagnosed, but prolonged intestinal virus shedding has been documented, thus potentially enabling fecal–oral transmission. However, the infectious potential of SARS-CoV-2 viruses excreted with feces has remained unclear. Here, we investigated 247 stool specimens from 213 pediatric patients to assess the prevalence of intestinal SARS-CoV-2 shedding in hospitalized children without or with COVID-19 and determined the infectious capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Studies excluded on full-text screening). Finally, we included 13 studies with a total of 1625 participants [19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies excluded on full-text screening). Finally, we included 13 studies with a total of 1625 participants [19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Resultsmentioning
confidence: 99%
“…A further study from India described a multicenter cohort study involving 55 patients (55 samples) attending hospitals who tested positive for SARS-CoV-2 between May 2020 and August 2021 [29]. A study from three clinical centres in Austria reported data on 206 hospitalised children diagnosed between December 2020 and June 2021 [30]. A study from Denmark reported data on 28 patients diagnosed between October 23, 2020, and March 17, 2021 [31].…”
Section: Resultsmentioning
confidence: 99%
“…How SARS-CoV-2 can promote NEC in neonates is still unclear, but we can hypothesize that the high affinity of the virus for the gut mucosa may have a role in such a process [108][109][110][111]. According to the most recent studies, the virus may induce a strong paracrine activation involving the release of certain enteric hormones able to promote intestinal functions (i.e., vasoactive intestinal peptide (VIP)) after binding with ACE2 receptors of the intestinal mucosa, as well as an intense local immune response [112][113][114][115][116][117][118]. Noteworthily, during the last decade, some clinical trials have been started to evaluate the therapeutic potential of colostrum to prevent and treat the risk of NEC in preterm and very low-birth-weight infants [119][120][121][122][123].…”
Section: The Role Of Intestinal Microbiotamentioning
confidence: 99%